Cryo-EM structures of the Synechocystis sp. PCC 6803 cytochrome b6f complex with and without the regulatory PetP subunit. Issue 13 (15th July 2022) - Proctor, Matthew S.; Malone, Lorna A.; Farmer, David A.; Swainsbury, David J.K.; Hawkings, Frederick R.; Pastorelli, Federica; Emrich-Mills, Thomas Z.; Siebert, C. Alistair; Hunter, C. Neil; Johnson, Matthew P.; Hitchcock, Andrew
Abstract : In oxygenic photosynthesis, the cytochrome b 6 f (cyt b 6 f ) complex links the linear electron transfer (LET) reactions occurring at photosystems I and II and generates a transmembrane proton gradient via the Q-cycle. In addition to this central role in LET, cyt b 6 f also participates in a range of processes including cyclic electron transfer (CET), state transitions and photosynthetic control. Many of the regulatory roles of cyt b 6 f are facilitated by auxiliary proteins that differ depending upon the species, yet because of their weak and transient nature the structural details of these interactions remain unknown. An apparent key player in the regulatory balance between LET and CET in cyanobacteria is PetP, a ∼10 kDa protein that is also found in red algae but not in green algae and plants. Here, we used cryogenic electron microscopy to determine the structure of the Synechocystis sp. PCC 6803 cyt b 6 f complex in the presence and absence of PetP. Our structures show that PetP interacts with the cytoplasmic side of cyt b 6 f, displacing the C-terminus of the PetG subunit and shielding the C-terminus of cytochrome b 6, which binds the heme c n cofactor that is suggested to mediate CET. The structures also highlight key differences in the mode of plastoquinone binding between cyanobacterial and plant cyt b 6 f complexes, which we suggest may reflect the unique combination of photosynthetic and respiratory electron transfer in cyanobacterial thylakoid membranes. The structure of cyt b 6 f from a model cyanobacterial species amenable to genetic engineering will enhance future site-directed mutagenesis studies of structure-function relationships in this crucial ET complex.